Izražanje spolske korelacije pri položajnih poimenovanjih v ruščini in slovenščini - Uhlik, Mladen (Slavistična revija, 2019)
The article focuses on some characteristics of gender marking in the case of professional designations in Russian and compares them with their Slovenian equivalents. In Russian sentences with attributive meaning, the use of masculine forms in subject complement is more frequent than in Slovenian. Since Russian feminatives are less productive than Slovenian ones, in some professional designations Russian uses "hybrid nouns" that can refer to both genders despite belonging to the first declension. The female referent in this case can be marked by analytical forms of the predicate (Vrač prišla 'The doctor arrived'). This type of agreement is less frequent in the case of noun phrases with modifiers (naša vrač 'our doctor', horošaja vrač 'a good doctor'), where, though the referent is a woman, the masculine form is preferred. In Slovenian, the referential gender is most commonly marked by feminine derived nouns, so its marking with analytical predicate forms is not typical. The only exception is the noun vodja 'leader', which lacks a feminative, and for that reason licenses the gender marking of the referential gender with its syntactical targets-predicate verbs (Obe vodji sta prišli 'Both leaders arrived') as well as modifiers within the framework of noun phrase (naša vodja 'our leader', umetniška vodja 'art director'). In contrast to Russian equivalents, the feminine forms of the modifier are used in non-nominative cases as well (Projekt smo oddali umetniški vodji 'The project was submitted to the art director').
Keywords: comparative studies; designations of professions; gender marking; položajna poimenovanja; pomensko ujemanje; primerjalne študije; referenčnost; referentiality; Russian language; ruščina; semantic agreement; Slovenian language; slovenščina; spolska korelacija